Pensamiento crítico y metacognición en el aula en estudiantes de primaria de la I.E.P.P.S.M.A N° 60066 Virgen de Lourdes Yanashi Maynas 2022 - Murayari Mendoza, Christian (2025)
The procedures and results of this study are presented concisely. The aim was to examine the relationship between critical thinking and metacognition levels in primary school students at I.E.P.P.S.M.A. No. 60066 Virgen de Lourdes Yanashi Maynas in 2022. The study employed field, cross-sectional, and bivariate designs, with a relational research approach. Two questionnaires were developed to collect data, which underwent validation by experts. A survey was conducted among 176 students, who constituted both the population and the sample. The study concluded that there is a significant ordinal categorical relationship between critical thinking and metacognition levels among the primary school students at I.E.P.P.S.M.A. No. 60066 Virgen de Lourdes. 46.6% of them exhibit a good level of critical thinking, which correlates with a good level of metacognition in 47.2% of the students. The analysis was carried out using the Kendall Tau-b coefficient, which yielded a value of 0.255 with an approximate significance of 0.001 (p < 0.05).